A History of Shi‘i Islam : By Farhad Daftary (London and New York: I.B. Tauris, in association with The Institute of Ismaili Studies, 2013. 315 pages.) (American Journal of Islam and Society, 2014)
Despite the progress made in the study of Shi‘i Islam, few publications providea comprehensive account of its history. Referring primarily to secondarysources, A History of Shi‘i Islam overviews key events going back to the timeof Prophet Muhammad to “clarify misunderstandings” and illustrate the variousShi‘i schools’ contribution to Islamic history. From an Ismaili Perspectivecould have been a helpful subtitle, as will be explained below.The book consists of six chapters: “Introduction: Progress in the Study ofShi‘i Islam,” “The Origins and Early History of Shi‘i Islam,” “The Ithna‘asharisor Twelvers,” “The Ismailis,” “The Zaydis,” and “The Nusayris or ‘Alawis,” respectively. A glossary is provided; however, not all of the terms used by theauthor are listed. Each chapter is divided into several subsections ...